Prediction of Family Functioning in Patients Candidate for Open-Heart Surgery Based on Interpersonal Dependency and Demographic Factors - Taherpoor, Parisa; Namvar, Hooman; Atashpour, Seyed Hamid (Mental Health and Lifestyle Journal, 2026)
This study aimed to predict family functioning in patients who are candidates for open-heart surgery based on interpersonal dependency and demographic variables. This descriptive-analytical study was conducted on 250 patients scheduled for open-heart surgery in cardiac centers. Participants were selected through simple random sampling based on predetermined inclusion criteria. Data were collected using the McMaster Family Assessment Device (FAD) and the Hirschfeld Interpersonal Dependency Questionnaire, along with a demographic checklist. Questionnaires were administered manually and online. Data cleaning and screening procedures were performed prior to statistical analysis. Descriptive and inferential analyses were conducted using SPSS, including correlations, multicollinearity tests, and multiple regression analysis (enter method). Family functioning served as the criterion variable, while interpersonal dependency and demographic characteristics were entered as predictors. Interpersonal dependency (β = 0.44, p = .001), education (β = 0.23, p = .040), age (β = 0.21, p = .014), and marital status (β = –0.17, p = .012) were significant predictors of family functioning. The regression model was significant (F(14, 235) = 6.79, p = .001), explaining 21% of the variance in family functioning (R² = 0.207). Multicollinearity diagnostics indicated acceptable tolerance and VIF values for all predictors. Other demographic variables—including spouse’s education, illness duration, number of children, income, occupation, and type of illness—were not significant predictors. Correlation analysis also showed a significant association between interpersonal dependency (r = 0.31) and family functioning (p < .05). Interpersonal dependency, education level, age, and marital status are significant predictors of family functioning among patients awaiting open-heart surgery, highlighting the importance of psychosocial and relational factors in treatment planning and preoperative care.